Work Discipline, Leadership, and Job Satisfaction on Organizational Commitment and Teacher Performance of State Junior High School in Bangko District, Rokan Hilir Regency - Oka Atika; Achmad Tavip Junaedi; Astri Ayu Purwati; Zainol Mustafa (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to determine and analyze the influence of work discipline, leadership, and job satisfaction on organizational commitment and teacher performance at the Bangko District Junior High School. The number of samples in this study was the entire population of the study as many as 48 PNS teachers at the Bangko District State Junior High School. Data analysis using Structural Equation Modeling (SEM) using SmartPLS 3.0 application. The results of this study indicate that work discipline has no significant effect on organizational commitment, leadership has a significant positive effect on organizational commitment, job satisfaction has no significant effect on organizational commitment, work discipline has a significant positive effect on teacher performance, leadership has no significant effect on teacher performance, job satisfaction does not have a significant effect on teacher performance, and organizational commitment has no significant effect on teacher performance.